Uji Ketahanan Beberapa Varietas Jagung (Zea mays L.) Terhadap Intensitas Serangan Penyakit Bulai (Peronosclerospora maydis) - J, Pajrin; Panggeso, Johanis; I, Rosmini (AGROTEKBIS, 2013)
The research was conducted in the Soulowe of village, District Biromaru, Sigi. Experimental design used was Randomized Block Design (RBD) with 3 (three) treatments and 5 (five) replications, in order to obtain 15 units of the experiment.  Each treatment is based on the differences in varieties. These varieties are varieties Bonanza, Paramita and Kumala. The variables measured were the intensity of the attacks and the rate of infection diseases. The first observation made at the time the plant was 14 days after planting, subsequent observations made at intervals of once a week as much as 7 times. The results of this study showed that the difference in response of resistance varieties Bonanza, Paramita and Kumala against downy mildew caused by the fungus Peronosclerospora maydis. The highest attack intensity was found in varieties Bonanza followed by Kumala varieties, while the lowest was found in varieties Paramita. The highest disease infection rate was varietas Bonanza, then followed by Kumala varietas, and then Paramita varieties that have the lowest disease infection rate.